QUO VADIS PENDIDIKAN MULTIKULTURAL DALAM ERA GLOBAL DI PESANTREN - Choiri, Moh Miftahul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Historically, schools are educational institutions that are identical to the meaning of the typical Islamic Indonesia. As an educational institution "native Indonesia", boarding schools have a strong influence in shaping and maintaining social, cultural, political and religious people of Indonesia, especially Java, because the term evolved pesantren in Java. In the era of globalization, there is a contradiction between the global and local values. Form of opposition, including the cultural uniformity which is controlled by the big nations and developed nations such as Europe and the United States. Therefore, schools as institutions of traditional Islamic education in Indonesia has the challenge of playing a role in welcoming the era of globalization, especially to guard the positive cultures of traditional Islam which is rooted in the community, especially the local culture. Through multicultural education, schools are expected to see the urgency of the culture that had been developed in the community, particularly the Muslim community and bridging the cultural problem that is increasingly worrying.ØªØ§Ø±ÙØ®ÙØ§Ø ÙØ§ÙÙØ¯Ø§Ø±Ø³ ÙØ§ÙÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙÙØ© Ø§ÙØªÙ ÙÙ ÙØ·Ø§Ø¨ÙØ© ÙÙØ¹ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§ Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙÙÙÙØ°Ø¬ÙØ©. Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù "Ø§ÙØ¯ÙÙÙØ³ÙØ§ Ø§ÙØ£Ù" Ø§ÙÙØ¤Ø³Ø³Ø© Ø§ÙØªØ¹ÙÙÙÙØ©Ø ÙØ§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙØ§ ØªØ£Ø«ÙØ± ÙÙÙ ÙÙ ØªØ´ÙÙÙ ÙØ§ÙØÙØ§Ø¸ Ø¹ÙÙ Ø§ÙÙØ§Ø³ Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ© ÙØ§ÙØ«ÙØ§ÙÙØ© ÙØ§ÙØ³ÙØ§Ø³ÙØ© ÙØ§ÙØ¯ÙÙÙØ© ÙÙ Ø§ÙØ¯ÙÙÙØ³ÙØ§Ø ÙØ®ØµÙØµØ§ Ø¬Ø§ÙØ© Ø ÙØ£Ù ÙØµØ·ÙØ ØªØ·ÙØ±Øª Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØ¯Ø§Ø®ÙÙØ© ÙÙ Ø¬Ø§ÙØ§. ÙÙ Ø¹ØµØ± Ø§ÙØ¹ÙÙÙØ© Ø ÙÙØ§Ù ØªÙØ§ÙØ¶ Ø¨ÙÙ Ø§ÙÙÙÙ Ø§ÙØ¹Ø§ÙÙÙØ© ÙØ§ÙÙØÙÙØ©. Ø´ÙÙ ÙÙ Ø£Ø´ÙØ§Ù Ø§ÙÙØ¹Ø§Ø±Ø¶Ø© Ø Ø¨ÙØ§ ÙÙ Ø°ÙÙ Ø§ÙØªÙØ§Ø«Ù Ø§ÙØ«ÙØ§ÙÙ Ø§ÙØ°Ù ØªØ³ÙØ·Ø± Ø¹ÙÙÙ Ø§ÙØ¯ÙÙ Ø§ÙÙØ¨Ø±Ù ÙØ§ÙØ¯ÙÙ Ø§ÙÙØªÙØ¯ÙØ© ÙØ«Ù Ø£ÙØ±ÙØ¨Ø§ ÙØ§ÙÙÙØ§ÙØ§Øª Ø§ÙÙØªØØ¯Ø©. ÙÙØ°ÙÙØ ÙØ§ÙÙØ¯Ø§Ø±Ø³ ÙÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¥Ø³ÙØ§ÙÙ Ø§ÙØªÙÙÙØ¯Ù ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§ ÙØ§ÙØªØØ¯Ù Ø§ÙÙØªÙØ«Ù ÙÙ ÙØ¹Ø¨ Ø¯ÙØ± ÙÙ Ø§ÙØªØ±ØÙØ¨ Ø¹ØµØ± Ø§ÙØ¹ÙÙÙØ©Ø ÙØ§ Ø³ÙÙØ§ ÙØØ±Ø§Ø³Ø© Ø«ÙØ§ÙØ§Øª Ø¥ÙØ¬Ø§Ø¨ÙØ© Ø¹Ù Ø§ÙØ¥Ø³ÙØ§Ù Ø§ÙØªÙÙÙØ¯Ù Ø§ÙÙØªØ¬Ø°Ø± ÙÙ Ø§ÙÙØ¬ØªÙØ¹Ø ÙØ¨Ø®Ø§ØµØ© Ø§ÙØ«ÙØ§ÙØ© Ø§ÙÙØÙÙØ©. ÙÙ Ø®ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ ÙØªØ¹Ø¯Ø¯ Ø§ÙØ«ÙØ§ÙØ§Øª Ø ÙÙÙ Ø§ÙÙØªÙÙØ¹ Ø£Ù Ø§ÙÙØ¯Ø§Ø±Ø³ ÙÙØ¹Ø±ÙØ© Ø§ÙØØ§Ø¬Ø© Ø§ÙÙÙØØ© ÙÙØ«ÙØ§ÙØ© Ø§ÙØªÙ ØªÙ ÙØ¶Ø¹ÙØ§ ÙÙ Ø§ÙÙØ¬ØªÙØ¹Ø ÙÙØ§Ø³ÙÙØ§ Ø§ÙÙØ¬ØªÙØ¹ ÙØ³ÙÙ ÙØ±Ø¯Ù Ø§ÙÙØ´ÙÙØ© Ø§ÙØ«ÙØ§ÙÙØ© Ø§ÙØªÙ ØªØ¨Ø¹Ø« Ø¹ÙÙ Ø§ÙÙÙÙ Ø¨Ø´ÙÙ ÙØªØ²Ø§ÙØ¯